Protonation of rhodanine polymers for enhancing the capture and recovery of Ag+ from highly acidic wastewater. Issue 11 (1st October 2019) - Yin, Xiaocui; Shao, Penghui; Ding, Lin; Xi, Yu; Zhang, Kai; Yang, Liming; Shi, Hui; Luo, Xubiao
Abstract : Contraposing nature of actual Ag-polluted water, poly-allylrhodanine is designed and synthesized, which achieves superior capacity, outstanding selectivity and ultrahigh purity of reclaimed Ag + in capture of Ag + from highly acidic wastewater. Abstract : Selective capture and direct recovery of silver ions from highly acidic wastewater are desirable but challenging for sustainable remediation of contamination. In this work, contraposing the characteristics of actual Ag-polluted water, poly-allylrhodanine (PAR) is designed and synthesized as an adsorbent. Different from most reported adsorbents, PAR features a unique acidity-enhanced adsorptivity property, thus achieving an ultrahigh capacity (651.0 mg g −1 ) and outstanding selectivity (>100) in the capture of Ag + from wastewater with strong acidity (pH −0.2). Moreover, the purity of the reclaimed Ag + reaches up to 99.80%, delivering an enormous economic benefit. Further characterization and theoretical calculations uncover that the CS and C–S groups on PAR act as adsorption sites to coordinate the Ag + ions via a special pH-dependent protonation exchange mechanism. In the treatment of actual Ag-polluted water, the treatment capacity of PAR is as high as 4015 bed volumes (BV) per run at pH = −0.2, which is 100-fold higher than that of commercial resin, highlighting its great potential in practical applications. The wastewater feature-directed design concept and the high-performance adsorbent of PAR reported in this work may be helpful to fill the gap between the experimental laboratory and practical remediation of Ag-containing wastewater.